Role of Image in Greek-Turkish Relations - (:unkn) unknown (Peter Lang AG, 2018)
This volume evaluates the role of image reconstruction processes in Greek-Turkish relations in the last decades. With contributions from prominent academics from different social science disciplines, it explains various aspects of contemporary image construction processes through educational materials in schools, history books, media, popular culture, cinema, diplomatic and political discourses. The authors explain how images about Self and the Other are reconstructed through different social interaction processes of individuals today and how much the new images differ from the Others offered by nationalist rhetoric of nation states. They analyze the limits of alternative image construction processes in eroding settled national images. © Peter Lang GmbH Internationaler Verlag der Wissenschaften Berlin 2018.